2021
DOI: 10.3390/foods10081759
|View full text |Cite
|
Sign up to set email alerts
|

Waste Bread as Main Ingredient for Cookie Elaboration

Abstract: Food waste is a current global problem. The aim of this work was to investigate the possibility of reintroducing bread discarded by retailers in the preparation of sugar-snap cookies. Bread flours were obtained from stale breads (white and whole wheat) milled with 200, 500 and 1000 μm sieves. Cookies were elaborated using 100% bread flours and combinations of 50% of bread flour and wheat flour. The rheology of the doughs, the dimensions of the cookies, their texture and colour were evaluated. Bread flour dough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Fernández-Peláez et al 13 characterized the physical properties of flours obtained from bread waste. Guerra-Oliveira et al 14 used BWF as a 50% replacer of wheat flour in cookie formulations. These studies have shown that the recycling of waste bread is a viable option for developing food products in the context of sustainability and a circular economy.…”
Section: Introductionmentioning
confidence: 99%
“…Fernández-Peláez et al 13 characterized the physical properties of flours obtained from bread waste. Guerra-Oliveira et al 14 used BWF as a 50% replacer of wheat flour in cookie formulations. These studies have shown that the recycling of waste bread is a viable option for developing food products in the context of sustainability and a circular economy.…”
Section: Introductionmentioning
confidence: 99%
“…The use of bread flour in the production of snacks (Samray et al ., 2019), sourdough (Gélinas et al ., 1999), bread (Meral & Karaoğlu, 2020) and cookies (Guerra‐Oliveira et al ., 2021) has been studied. Flours obtained from bread crust or crumb of different bread types have also been characterised (Fernández‐Peláez et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are similar to those obtained by Cardoso et al ( 2019) on wheat and rye flours, but in this research, mold and yeast counts are somewhat lower. These would suggest that the flours from these types of bread could be used for human food, such as the production of cookies (Guerra-Oliveira et al, 2021) or cakes (Guerra-Oliveira et al, 2022), and thus reduce food waste. Alpers et al (2021) argue that the absence of visual detection is sufficient to eliminate the risk of mycotoxin growth.…”
Section: Resultsmentioning
confidence: 99%
“…In households, stale bread is often ground and used in several culinary recipes. Considering that bread is wasted throughout the food supply chain, the industry sector has come up with several options for its reuse, such as the preparation of sourdoughs (Gélinas, McKinnon, & Pelletier, 1999), cookies (Guerra-Oliveira, Belorio, & Gómez, 2021), cakes (Guerra-Oliveira, Belorio, & Gómez, 2022), snacks (Samray, Masatcioglu, & Koksel, 2019), and beer (Brancoli, Bolton, & Eriksson, 2020).…”
Section: Introductionmentioning
confidence: 99%